2021
DOI: 10.3390/f12081134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Remote Sensing for the Assessment and Monitoring of Forest Health: A Systematic Evidence Synthesis

Abstract: Forests are increasingly subject to a number of disturbances that can adversely influence their health. Remote sensing offers an efficient alternative for assessing and monitoring forest health. A myriad of methods based upon remotely sensed data have been developed, tailored to the different definitions of forest health considered, and covering a broad range of spatial and temporal scales. The purpose of this review paper is to identify and analyse studies that addressed forest health issues applying remote s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 179 publications
0
24
0
Order By: Relevance
“…The remote sensing image data provided useful information for the detection of the damages caused by bark beetles and root rot disease outbreaks. Analyses of remote sensing techniques in 107 journal papers published between 2015 and 2020 showed that, despite the emergence of new technologies and methods, multispectral data are still the prevalent source in forest health assessment [14]. However, in the Polish part of the Białowie ża Forest, the spread of the I. typographus outbreak was estimated by mapping dead spruce stands on a tree level using airborne hyperspectral and laser scanning data obtained from HySpex VNIR-1800 camera and Riegl LMS-Q680i scanner [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The remote sensing image data provided useful information for the detection of the damages caused by bark beetles and root rot disease outbreaks. Analyses of remote sensing techniques in 107 journal papers published between 2015 and 2020 showed that, despite the emergence of new technologies and methods, multispectral data are still the prevalent source in forest health assessment [14]. However, in the Polish part of the Białowie ża Forest, the spread of the I. typographus outbreak was estimated by mapping dead spruce stands on a tree level using airborne hyperspectral and laser scanning data obtained from HySpex VNIR-1800 camera and Riegl LMS-Q680i scanner [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the utility of optical remote sensing for assessing a variety of forest health indices, and are commonly used in forest monitoring activities (Curran et al, 1992; Huang et al, 2019; Parent & Verbyla, 2010). Landsat satellite images are still the most widely used Earth Observation (EO) data in forest health studies (Torres et al, 2021), which provide continuous time series data from the 1970s (i.e., Landsat 1 mission) until today (i.e., Landsat 8). Access to Landsat images has been free since 2008, and the recently launched Landsat 9 (September 2021) will be publicly available in early 2022.…”
Section: Assessing Air Pollution: Research Infrastructures and Method...mentioning
confidence: 99%
“…Satellite-based RS still dominates forest health research. The most frequently used data are publicly accessible imagery such as Landsat, MODIS, and Sentinel [19]. The large area coverage makes satellites valuable tools at multiple scales.…”
Section: Uav Remote Sensing: An Emerging Tool In Forest Health Monito...mentioning
confidence: 99%